Benthic stable isotope record of ODP Site 208-1263 - Vittoria Lauretano; James C Zachos; Lucas Joost Lourens (PANGAEA, 2018)
The late Paleocene to early Eocene warming trend was punctuated by a series of orbitally paced transient warming events, associated with the release of isotopically light carbon into the ocean-atmosphere system. These events occurred throughout the early Eocene, critically persisting during onset, peak, and termination of the Early Eocene Climatic Optimum (EECO) and the onset of the middle Eocene cooling. Here we present a ~5.2 million-year (Myr) long high-resolution benthic foraminiferal stable-isotope record spanning the peak of the early Eocene “hothouse” from Ocean Drilling Program (ODP) Leg 208 Site 1263. Our new oxygen isotope record confirms the presence of short-term warming events during the peak and termination of the EECO, previously described in coeval bulk carbonate records. The degree of change between deep-sea temperature and concurrent carbon release during these events is consistent with previous findings for Eocene Thermal Maximum (ETM) 2 to 3, suggesting that the orbitally forced processes that triggered these perturbations in the exogenic carbon pool were similar. Additionally, the long-term background carbon isotope signature reveals a rapid enrichment of up to ~1.0 extperthousand across the peak warmth of the EECO, ~51.6 Ma, without a corresponding shift in the oxygen record suggesting a decoupling from climate. We speculate that this carbon shift reflects a non-recurrent adjustment in the mean (steady) state of the deep ocean carbon reservoir due to a significant change in carbon source/sink, the biological pump and/or ocean circulation during the extreme greenhouse conditions of the EECO.
Supplement to: Lauretano, V et al. (2018): Orbitally Paced Carbon and Deep-Sea Temperature Changes at the Peak of the Early Eocene Climatic Optimum. Paleoceanography and Paleoclimatology, https://doi.org/10.1029/2018PA003422